A Combination of Two Antioxidants (An SOD Mimic and Ascorbate) Produces a Pro-Oxidative Effect Forcing Escherichia coli to Adapt Via Induction of oxyR Regulon - Batinic-Haberle, Ines; Rajic, Zrinka; Benov, Ludmil (Anti-Cancer Agents in Medicinal Chemistry, 2011)
Cationic Mn(III) N-alkylpyridyl (MnTalkyl-2(or 3)-PyP5+) and N, N'-dialkylimidazolylporphyrins (MnTDalkyl-2-ImP5+) have been regarded as the most powerful SOD mimics/peroxynitrite scavengers - i. e. antioxidants. The ethyl-, MnTE-2-PyP5+ (AEOL10113), and hexylpyridyl-, MnTnHex-2-PyP5+ and diethylimidazolylporphyrin, MnTDE-2-ImP5+ (AEOL10150) have been mostly studied in vitro and in vivo. Given the in vivo abundance of cellular reductants, MnPs can couple with them in removing superoxide. Thus, they could be readily reduced from MnIIIP to MnIIP with ascorbate and glutathione, and in a subsequent step reduce either O2 .- (while acting as superoxide reductase) or oxygen (while exerting pro-oxidative action). Moreover, MnPs can catalyze ascorbate oxidation and in turn hydrogen peroxide production. The in vivo type of MnP action (anti- or pro-oxidative) will depend upon the cellular levels of reactive species, endogenous antioxidants, availability of oxygen, ratio of O2 .– to peroxide-removing systems, redox ability of MnPs and their cellular localization/bioavailibility. To exemplify the switch from an anti- to pro-oxidative action we have explored a very simple and straightforward system - the superoxide-specific aerobic growth of SOD-deficient E. coli. In such a system, cationic MnPs, ortho and meta MnTE-2-(or 3)-PyP5+ act as powerful SOD mimics. Yet, in the presence of exogenous ascorbate, the SOD mimics catalyze the H2O2 production, causing oxidative damage to both wild and SOD-deficient strains and inhibiting their growth. Catalase added to the medium reversed the effect indicating that H2O2 is a major damaging/signaling species involved in cell growth suppression. The experiments with oxyR- and soxRS-deficient E. coli were conducted to show that E. coli responds to increased oxidative stress exerted by MnP/ascorbate system by induction of oxyR regulon and thus upregulation of antioxidative defenses such as catalases and peroxidases. As anticipated, when catalase was added into medium to remove H2O2, E. coli did not respond with upregulation of its own antioxidant systems.
Keywords: glutathione